部分積分と繰り返し部分積分

部分積分と繰り返し部分積分

(1)部分積分

\[ \int f(x)g(x)dx=f^{(-1)}(x)g(x)-\int f^{(-1)}(x)g^{(1)}(x)dx \]

(2)繰り返し部分積分

\(n\in\mathbb{N}_{0}\)とする。

\[ \int f(x)g(x)dx=\sum_{k=0}^{n-1}\left(-1\right)^{k}f^{(-(k+1))}(x)g^{(k)}(x)+(-1)^{n}\int f^{(-n)}(x)g^{(n)}(x)dx \]

(1)

\begin{align*} \int f(x)g(x)dx & =\int\left\{ \left(f^{(-1)}(x)g(x)\right)'-f^{(-1)}(x)g^{(1)}(x)\right\} dx\\ & =f^{(-1)}(x)g(x)-\int f^{(-1)}(x)g^{(1)}(x)dx \end{align*}

(2)

\[ \int f^{(-k)}(x)g^{(k)}(x)dx=f^{(-(k+1))}(x)g^{(k)}(x)-\int f^{(-(k+1))}(x)g^{(k+1)}(x)dx \]

より、

\[ (-1)^{k+1}\int f^{(-(k+1))}(x)g^{(k+1)}(x)dx=(-1)^{k}\int f^{(-k)}(x)g^{(k)}(x)dx+(-1)^{k+1}f^{(-(k+1))}(x)g^{(k)}(x) \]

となるので、

\begin{align*} \int f(x)g(x)dx & =\sum_{k=0}^{n-1}\left((-1)^{k}\int f^{(-k)}(x)g^{(k)}(x)dx-(-1)^{k+1}\int f^{(-(k+1))}(x)g^{(k+1)}(x)dx\right)+(-1)^{n}\int f^{(-n)}(x)g^{(n)}(x)dx\\ & =\sum_{k=0}^{n-1}\left(-(-1)^{k+1}f^{(-(k+1))}(x)g^{(k)}(x)\right)+(-1)^{n}\int f^{(-n)}(x)g^{(n)}(x)dx\\ & =\sum_{k=0}^{n-1}\left((-1)^{k}f^{(-(k+1))}(x)g^{(k)}(x)\right)+(-1)^{n}\int f^{(-n)}(x)g^{(n)}(x)dx \end{align*}

ページ情報

タイトル

部分積分と繰り返し部分積分

URL

https://www.nomuramath.com/l2cjw2q1/

SNSボタン